Blood-flow restriction is associated with more even pacing during high-intensity cycling - Smith, N. D. W.; Abbiss, C. R.; Girard, O.; Scott, B. R.; Peiffer, J. J. (International Journal of Sports Physiology and Performance, 2023)
Purpose: This study examined the influence of blood-flow restriction (BFR) on the distribution of pace, physiological demands, and perceptual responses during self-paced cycling.